Human newborns form musical predictions based on rhythmic but not melodic structure - Bianco, Roberta; Tóth, Brigitta; Bigand, Felix; Nguyen, Trinh; Sziller, István; Háden, Gábor P.; Winkler, István; Novembre, Giacomo (PLOS Biology, 2026)
The ability to anticipate rhythmic and melodic structures in music is considered a fundamental human trait, present across all cultures and predating linguistic comprehension in human development. Yet, it remains unclear the extent to which this ability is already developed at birth. Here, we used temporal response functions to assess rhythmic and melodic neural encoding in newborns (N = 49) exposed to classical monophonic musical pieces (real condition) and control stimuli with shuffled tones and inter-onset intervals (shuffled condition). We computationally quantified context-based rhythmic and melodic expectations and dissociated these high-level processes from low-level acoustic tracking, such as local changes in timing and pitch. We observed encoding of probabilistic rhythmic expectations only in response to real but not shuffled music. This proves newborns’ ability to rely on rhythmic statistical regularities to generate musical expectations. We found no evidence for the tracking of melodic information, demonstrating a downweighting of this dimension compared to the rhythmic one. This study provides neurophysiological evidence that the capacity to track statistical regularities in music is present at birth and driven by rhythm. Melodic tracking, in contrast, may receive more weight through development with exposure to signals relevant to communication, such as speech and music.